Vulnerabilidade social no Brasil: Conceitos, métodos e primeiros resultados para municípios e regi\~oes metropolitanas brasileiras - Marco Aurélio Costa; Maria Paula Gomes dos Santos; Bárbara Marguti; Nikolas Pirani; Carlos Vinicius da Silva Pinto; Rodrigo Luis Comini Curi; Clarisse Coutinho Ribeiro; Clayton Gurgel de Albuquerque (Instituto de Pesquisa Econômica Aplicada (IPEA), 2018)
– The Índice de Vulnerabilidade Social (IVS) and the Atlas da Vulnerabilidade Social (AVS) of the municipalities and metropolitan regions arise by an effort of selection, development and georeferencing of indicators that could express conditions of social vulnerability in the different scales of brazilian territory. Such conditions may emerge from plural factors that are part of the social issue, like the contexts of income and labour, education and health, mobility, habitation and sanitation. The IVS is a sinthetic index constructed with indicators that express fragilities of this social factors. The text below presentes the process of criation of the IVS from your conceptual, methodological and statiscal aspects and limitations. After this presentation, the work will show na analysis of some IVS results, as well as your dimensions and indicatores for the years of 2000 e 2010, in order to delineate the conditions of social vulnerability in the brazilian territory and exemplify ways of data analysis available in the AVS.
Keywords: O15; O18; R23; J15; 330; social vulnerability; sinthetic index; Brazil; public policy; regional development